Diffusion Weighted Imaging and Apparent Diffusion Coefficient in 3 Tesla Magnetic Resonance Imaging of Breast Lesions. (28th May 2015) - Caivano, Rocchina; Villonio, Antonio; D' Antuono, Felice; Gioioso, Matilde; Rabasco, Paola; Iannelli, Giancarlo; Zandolino, Alexis; Lotumolo, Antonella; Dinardo, Giuseppina; Macarini, Luca; Guglielmi, Giuseppe; Cammarota, Aldo
<x xml:space="preserve">Abstract</x> Objective: To evaluate the utility of diffusion-weighted-imaging (DWI) and apparent-diffusion-coefficient (ADC) in a 3T magnetic-resonance-imaging (MRI) study of breast cancer. In particular, the study aims to classify ADC-values according to histology either for benign or malignant lesions. Methods: 110 Breast MRI with MRI-DWI sequences and quantitative evaluation of the ADC were retrospectively reviewed. Results obtained with MRI-DWI and with biopsy were analyzed and ADC values were compared to histological results. Results: MRI showed a 95.5% sensitivity and a 83.7% specificity. The mean ADC values of benign and malignant lesions were 2.06 ± 0.19 and 1.03 ± 0.07 mm2/s, respectively (p < .05). Conclusions: DWI and ADC-values could help distinguishing malignant and benign breast masses.